Comparison of the Effectiveness of Using Baamboozle and Concrete Manipulative Learning Media on Students’ Learning Outcomes in the SKI Subject at MAN 3 Mataram - Aulya Amanda; Wildan Wildan (AS-SABIQUN, 2026)
The limited comparative research on digital game-based learning media and concrete manipulative media in improving students’ learning outcomes in Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) at the madrasah level highlights the need for evidence-based evaluation of interactive instructional approaches. This study aims to analyze the comparative effectiveness of Baamboozle learning media, concrete manipulative media, and conventional teaching methods on students’ SKI learning outcomes at MAN 3 Mataram. A quantitative quasi-experimental design with a posttest-only control group approach was employed. The sample consisted of 72 students selected through random sampling and divided into three groups: the Baamboozle experimental group, the concrete manipulative experimental group, and the control group. Data were collected using a cognitive learning achievement test consisting of 40 multiple-choice items and analyzed using descriptive statistics, normality and homogeneity tests, One-Way ANOVA, and Tukey HSD post hoc analysis with SPSS 24. The findings revealed significant differences among the three instructional groups, with the Baamboozle group achieving the highest learning outcomes. The ANOVA results showed a statistically significant difference among groups, p < .001, and the Tukey HSD analysis demonstrated that the Baamboozle group significantly outperformed both the concrete manipulative and control groups. These findings indicate that Baamboozle-based learning media are more effective in improving students’ SKI learning outcomes by promoting active participation and learning motivation through game-based activities. This study contributes to Islamic education by providing empirical evidence on the value of technology-integrated learning and supports the use of interactive digital media to enhance instructional quality in madrasah classrooms.